KUALITAS PELAYANAN PEMBUATAN PASPOR DI KANTOR IMIGRASI KELAS II KOTA CILACAP - Iswari, Sutiyani Yoga; Warsono, Hardi; Rengga, Aloysius (Journal of Public Policy and Management Review, 2013)
Understanding the procedures of making the given passport has existed and been good. But less understood by the general population of executives who take care of passport directly on its own, because the procedure is believed to be less obvious, less informative giving rise to confusion. In addition, the perception of the ability of employees in the process of making a passport applicant making a sluggish feel aggrieved. The purpose of this study was to determine the relationship between variables, the procedure is understanding the perceptions of service quality and personnel capacity is partial and simultaneous. Samples are taken using incidental sampling of 95 respondents. The Data obtained were analyzed using rank correlation coefficient method of kendall, kendall and konkordasi coefficient coefficient of determination. The results of this study indicate that there is a positive relationship between the variables, the procedure is understanding the perceptions of service quality and personnel capacity is partial and simultaneous, with the magnitude of the relationship between the variables of understanding the procedure and the perception of the ability of employees to quality service categories include 100% perfect relationship. The suggestion of this research is to improve the quality of service it is necessary the presence of the addition of facilities and infrastructure repair and provide services that are more oriented to the applicant.